67. Impact of Riluzole on the effects of paired associative stimulation (PAS) on cortical excitability in ALS patients. Issue 12 (December 2016) - Ceccanti, M.; Cambieri, C.; Onesti, E.; Tartaglia, G.; Frasca, V.; Rubino, A.; Inghilleri, M.
Abstract : Amyotrophic lateral sclerosis (ALS) is a degenerative disease involving upper and lower motor neurons. Paired associative stimulation (PAS) is an experimental method to investigate synaptic plasticity through LTP-like changes. Purpose of this study is to evaluate PAS effects on M1 excitability in ALS patients before and after two weeks of Riluzole intake. Eighteen ALS patients (nine pseudobulbar, nine spinal) have been recruited; we evaluated average amplitude of ten MEPs (120% of resting motor threshold -RMT-) before PAS protocol, right after (T0) and after 10 (T10), 20 (T20), 30 (T30) and 60 (T60) minutes. PAS protocol consisted in 200 electrical stimulus at 0.3 Hz, delivered on median nerve of non-dominant hand (300% sensitive threshold, 500 mcs), associated to a magnetic stimulus at 100% of RMT upon contralateral motor cortex. Interstimulus interval was decided according to latency of the component N20 of SEP, delayed by 2 ms. Repeated measures ANOVA showed a trend to significance in MEP amplitude increase in T20 and T30 ( p  = 0.066 and 0.057 respectively) and a significant increase in T60 ( p  = 0.047) in patients without Riluzole. In patients assuming Riluzole, no significant change in MEP amplitude was found. Riluzole could impair sensory-motor integrative circuits, as evaluated by PAS protocol.